Phenolic and furanic compounds of Portuguese chestnut and French, American and Portuguese oak wood chips - Garcia, Raquel (2012)
Botanical species used on aging process must be wisely and judiciously chosen, and for this selection, a basic knowledge of the chemical composition of woods is warranted. Aiming to contribute to extend the knowledge of the chemical composition of several wood species useful for enological purposes, we have focused our studies on Portuguese chestnut and French, American and Portuguese oak chips. The profile of low molecular weight phenolic composition of these chips was achieved, using an optimized extraction method based on pressurized liquid extraction, followed by the quantification of phenolic acids, phenolic aldehydes and furanic derivatives by high-performance liquid chromatography (HPLC-DAD). The identification of those compounds was also confirmed by LC-DAD/ESI-MS. This study allowed the determination of the low molecular phenolic composition of Portuguese chestnut and French, American and Portuguese oak wood. According to our results, the influence of the botanical species seems to be more relevant than the geographic origin of the wood species.